Interactive Collaboration Platform in Augmented Reality - João Pedro Miranda Maia (2017)
Numerous tools are used for remote collaboration, however, they restrict the users to a very confined virtual space and restrain interaction with the remote physical world. This project proposes an Augmented Reality (AR) framework for remote collaboration, in which the remote user creates instructions in a 3D virtual space which mimics the local user's environment. The instructions are then presented to the local user using augmented reality, linking the virtual and real world. The local user tries to execute the task according to the virtual instructions. Subsequently, the remote user receives feedback back and, if positive, proceeds with the next set of instructions.